Scale-isometric polytopal graphs in hypercubes and cubic lattices : polytopes in hypercubes and Zn̳ - Deza, M., 1939- (Imperial College Press, 2004)
This monograph identifies polytopes that are "combinatorially l1-embeddable", within interesting lists of polytopal graphs, i.e. such that corresponding polytopes are either prominent mathematically (regular partitions, root lattices, uniform polytopes and so on), or applicable in chemistry (fullerenes, polycycles, etc.). The embeddability, if any, provides applications to chemical graphs and, in the first case, it gives new combinatorial perspective to "l2-prominent" affine polytopal objects. The lists of polytopal graphs in the book come from broad areas of geometry, crystallography and graph.